Improved Performance Through Empowerment of Small Industry - Purnama, Chamdan (Journal of Social Economics Research, 2014)
This research is intended to study how does the implementation of education and training, government assistance, business partnership, and government regulation effect business ability and business success? The sample of this research 174 small business units in east java province and selected by using stratified cluster sampling technique. Applying structural equation modeling analysis, the research findings are as follow. First, education and training with indicator charisma an instructor, instructor team cooperation, accuracy of method teach, motivation follow,according to its items have an effect on positive tobusiness ability but have not an effect to success of small business with indicator production efficiency and production extension. Second, government assistancewith indicator, technical assistance, guidance, management, financial and tuitionhaving an effect on positive toability and success of small. Third, business partnershipwith indicator, trade cooperation, network, contract sub, technological cooperation and vendorhave an effect on positive tobusiness ability with indicator attitude, emotional intelligence, skill and knowledge but have not an effect to success of small business. Fourth, regulation of governmentwith indicator, quota, tariff, licensing and market information have an effect on positive tobusiness ability with indicator attitude, emotional intelligence, skill and knowledge but have not an effect to success of small business with indicator production efficiency and production extension. Fifth, business ability have an effect to success of small business. From the finding 1 to 5, the researcher conclude that, to increase small business successis needed five variables observed (education and training, assistance, partnership, and regulation and business ability) and to increase business abilityis needed of the four variables observed (education and training, assistance, partnership, and regulation).